2016
DOI: 10.15288/jsad.2016.77.889
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Sensitivity and Distress Intolerance as Predictors of Cannabis Dependence Symptoms, Problems, and Craving: The Mediating Role of Coping Motives

Abstract: ABSTRACT. Objective:The tendency to react with fear to anxietyrelated sensations (anxiety sensitivity) and the inability to tolerate distressing psychological or physiological states (distress intolerance) are implicated in the comorbidity between affective psychopathology and cannabis use disorders. Emotionally vulnerable cannabis users may be particularly apt to use cannabis to cope with distress, which may both lead to and maintain its problematic use (e.g., dependence, craving). The current study tested a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 63 publications
(77 reference statements)
3
48
0
Order By: Relevance
“…; Farris et al . ). Somewhat consistent with predictions, cannabis cue‐elicited modulation of the LPP during acute stress was significantly related to three indices of cannabis problem severity among high DI users, although these effects were generally limited to the later time windows, and the relationship with the MPS was not robust to outlier exclusion.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…; Farris et al . ). Somewhat consistent with predictions, cannabis cue‐elicited modulation of the LPP during acute stress was significantly related to three indices of cannabis problem severity among high DI users, although these effects were generally limited to the later time windows, and the relationship with the MPS was not robust to outlier exclusion.…”
Section: Discussionmentioning
confidence: 71%
“…Recent studies have demonstrated that high distress intolerance (DI), an individual difference reflective of the ability to tolerate and effectively manage negative affect, is linked with CUD indices in regular users (Bujarski, Norberg & Copeland ; Farris et al . ). Further, these associations appear to be partially mediated by increased coping motives for cannabis use (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Two cross‐sectional studies examining the link between AS and alcohol‐related outcomes among adult smokers and people living with HIV/AIDS, respectively, found that difficulties with emotion regulation mediated the relationship between AS and hazardous drinking (Paulus, Jardin, et al., ; Paulus et al., ), suggesting the potential additional role of maladaptive regulation of negative affect in the link between AS and alcohol use in these medical populations. There is also some evidence of a link between AS and increased cannabis use (Paulus, Manning, Hogan, & Zvolensky, ) and increased coping and conformity motives for use (Bonn‐Miller, Zvolensky, & Bernstein, ; Zvolensky, Marshall, et al., ), although a recent cross‐sectional study found that lower distress tolerance was associated with increased cannabis dependence symptoms and stronger coping motives, whereas AS was not (Farris, Metrik, Bonn‐Miller, Kahler, & Zvolensky, ). Further, individuals with high AS demonstrate a propensity to use alcohol and tobacco specifically to cope with distress (e.g., Brown, Kahler, Zvolensky, Lejuez, & Ramsey, ; Woicik et al., ), again suggesting that tension reduction is a primary motivation for their substance use, as McNally () suggested.…”
Section: Engagement In Maladaptive Health Behaviorsmentioning
confidence: 99%
“…Therefore, by increasing craving, they no longer consume Marijuana immediately. Similarly, with other DBT components, they learn reinforcement management and problem-solving skills that they can help MUD patients to reduce Marijuana consumption (20,22,24,27,28).…”
Section: Discussionmentioning
confidence: 99%